Optimalisasi Kemampuan Menyimak Peserta Didik melalui Penerapan Gamifikasi dalam Pembelajaran Bahasa Indonesia Kelas 5 SDN Gubeng 1 Surabaya - Alamsyah, Artika Devi; Wardana, Bayu Adi Putra; Sugiarsih, Septia (CV. Kurnia Grup, 2025)
This study aims to optimize the listening skills of fifth-grade students at SDN Gubeng 1 Surabaya through the application of gamification in Indonesian language learning. The background of this study stems from the low level of attention, motivation, and learning outcomes of students in conventional listening activities. The research used a one-group pretest-posttest pre-experimental design involving 25 students as research subjects. Data were collected through listening tests, participation observations, and documentation. The results showed a significant increase after the application of gamification. The average pretest score of 57.76 increased to 74.60 on the posttest, with an N-Gain value of 0.3987 (moderate category). The paired sample t-test yielded t = 12.6377 and a p-value < 0.05, which means there was a significant difference between the pretest and posttest results. In addition, student active participation increased from 60% to 85% after the implementation of gamification elements such as points, badges, challenges, and the “Simon Says” game. These findings indicate that gamification is effective in improving listening skills while encouraging student engagement and motivation to learn.